Experimental Performance Evaluation of a MR Brake-Based Haptic System for Teleoperation - Gang, Han Gyeol; Choi, Seung-Bok; Sohn, Jung Woo (Frontiers in Materials, 2019)
In this work, a new type of haptic system inspired by human wrist motion is proposed and its performances are evaluated experimentally for teleoperation. The master device has 3-DOF rotational motion as same as human wrist motion and semi-active MR brakes are installed to generate haptic effect for the operator. To achieve good haptic feedback effect, the master device is designed with lightweight structure and the haptic actuator is designed with minimal size. The slave robot has 3-DOF rotational motion using servomotors, five bar linkage mechanism and a pivot point. In the proposed slave robot, instead of commercial torque sensor, a self-designed torque sensor using three force sensors is adopted. It has been experimentally validated that the proposed haptic system has good performances on tracking control of desired position and repulsive torque. In addition, to ensure that the human operator can actually distinguish the difference of torque magnitude, a simple recognition test is also carried out. Although not continuous, it is confirmed that the torque difference can be distinguished in three levels. Then, it is demonstrated that the proposed haptic system can be effectively applied to real teleoperation system.